ANALYSIS OF THE RIGHTS OF SUSPECTS IN PRETRIAL DECISIONS IN MAKASSAR STATE COURT DECISION NUMBER 6/PID.PRA/2020/PN.MKS - Rahmat Islami; Andi Muh. Sofyan; Audyna Mayasari Muin (Jurnal Meta-Yuridis, 2023)
Makassar District Court Decision Number 8/Pid.Pra/2020/PN.Mks, present to annul Makassar District Court Decision Number 6/Pid.Pra/2020/PN.Mks. This means that there is a conflict between the two decisions, where the Makassar District Court Decision Number 6/Pid.Pra/2020/PN.Mks., should have been implemented before the Makassar District Court Decision Number 8/Pid.Pra/2020/PN.Mks. was issued. The above conditions cause the suspect's rights to not be exercised. as if the Makassar District Court Decision Number 6/Pid.Pra/2020/PN.Mks., is something that doesn't need to be implemented, even though it is a decision that has permanent legal force. This research is a normative research that is descriptive in nature, analyzes the judge's legal considerations in deciding the Pretrial Decision Number 6/Pid.Pra/2020/PN.Mks so that the applicant accepts the request based on juridical considerations, namely the suspect is not on DPO status, and the determination of the applicant as a suspect does not meet the evidence. enough start. Furthermore, the judge's legal considerations in deciding the Pretrial Decision Number 8/Pid.Pra/2020/PN.Mks., so that the applicant's application is accepted is based on juridical considerations, namely the issuance of SP3 by the Makassar Polrestabes which was carried out on a holiday, as well as the issuance of a complete letter of investigation results. by the public prosecutor (P-21).